Investigating the Impact of STEM Learning on Students’ Critical Thinking Skills through Hand-Made Projector Activity - Rizki Maulana Ashidiq; Nanang Winarno; Eka Cahya Prima; Ari Widodo; Chun-Yen Chang (Universitas Pendidikan Indonesia, 2024)
This research presents an investigation on the utilization of Science, Technology, Engineering, and Mathematics (STEM) with Project-Based Learning as experiment class treatment and project-based learning as control class treatment to investigate students' critical thinking in optical instruments lessons, with a particular focus on the development of handmade projectors. In Indonesian schools, where there is a lack of integration of the STEM and learning activity itself, it is still in the form of a direct transfer of knowledge from teachers to students. This research used quantitative research with a quasi-experimental design. The method for data collection is purposive random sampling. The research participant consists of 60 eighth-grade middle high school students in Bandung chosen based on a purposive random sampling technique. The data is obtained through five open-ended essay questions about critical thinking skills. The result shows that the independent t-test for students’ critical thinking is 0.081, which means there are no significant differences between the control and experiment classes. However, in the STEM Project-based learning model, The N-gain of students’ critical thinking skills is 0.718, which is a high improvement. Moreover, on Project-Based Learning, the N-gain of students’ critical thinking skills is 0.660, which is a medium improvement.